Astronomical Resources on the Internet. - Joseph R. Kraus; Peter Banholzer (Issues in Science and Technology Librarianship, 2002)
This webliography on astronomical resources is written for librarians who serve a scientific or technical clientele, and any person interested in learning more about astronomy and astronomical information services.